Direct seawater splitting for hydrogen production: Recent advances in materials synthesis and technological innovation - Yilin Zhao; Zhipeng Yu; Aimin Ge; Lujia Liu; Joaquim Luis Faria; Guiyin Xu; Meifang Zhu (Green Energy & Environment)
Direct seawater splitting has emerged as a popular and promising research direction for synthesising clean, green, non-polluting, and sustainable hydrogen energy without depending on high-purity water in the face of the world's shortage of fossil energy. However, efficient seawater splitting is hindered by slow kinetics caused by the ultra- low conductivity and the presence of bacteria, microorganisms, and stray ions in seawater. Additionally, producing hydrogen on an industrial scale is challenging due to the high production cost. The present review addresses these challenges from the catalyst point of view, namely, that designing catalysts with high catalytic activity and stability can directly affect the rate and effect of seawater splitting. From the ion transfer perspective, designing membranes can block harmful ions, improving the stability of seawater splitting. From the energy point of view, mixed seawater systems and self- powered systems also provide new and low-energy research systems for seawater splitting. Finally, ideas and directions for further research on direct seawater splitting in the future are pointed out, with the aim of achieving low-cost and high-efficiency hydrogen production.